PENGARUH CORPORATE SOCIAL RESPONBILITY TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN KELOMPOK LQ45 YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2014-2018 - BR Ginting, Bunga Hati (JURNAL RISET AKUNTANSI TIRTAYASA, 2020)
This study aims to determine the effect of corporate social responbility on corporate value by profitability as a moderating variable. This research was conducted on LQ45 category companies on Indonesia Stock Exchange (BEI) period 2014-2018. The population in this study amounted to 45 companies. The sample was chosen by purposive sampling technique, so that the total sample was 8 companies. Data testing method used is linier regression analysis and moderated regression analysis (MRA). The results of this research show that corporate social responbility has positive effect on corporate value. Profitability strengthens the influence of corporate social responsibility on corporate value.Â